BATTLING THE UNCOMMON: A CASE REPORT ON ECTOPIC ACTH SYNDROME FROM PANCREATIC NEUROENDOCRINE TUMOUR WITH LIVER METASTASES - Ros, Muhammad Faiz Che; Hui, Khaw Chong; Azmi, Nor Shaffinaz Yusof; Abdullah, Noor Rafhati Adyani (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Introduction/Background Pancreatic neuroendocrine tumours (pNETs) are rare malignancies originating from the islet cells of the pancreas, comprising only 1%-2% of pancreatic tumours. Among functional pNETs, insulinoma and gastrinoma are the most common, while ACTH-secreting tumours are very rare. Ectopic ACTH syndrome (EAS) caused by pNETs is particularly aggressive, often presenting with metastatic disease, primarily to the liver. Case We present a case of a 25-year-old male who presented acutely with upper gastrointestinal bleeding. Clinical examination revealed features consistent with Cushing’s syndrome, and further investigations identified an ACTHsecreting neuroendocrine pancreatic tumour with liver metastasis. The disease was complicated by extensive inferior vena cava thrombosis and concurrent thrombocytopenia, necessitating the insertion of an IVC filter. The patient underwent distal pancreatectomy, splenectomy and wedge resection of the stomach. Hypercortisolism was controlled with steroidogenesis inhibitors, including metyrapone, ketoconazole and the newer agent, osilodrostat. Postoperatively, he underwent a Ga-68 Dotatate scan which showed evidence of somatostatin-receptor avid metastatic disease in the liver and he was started on a somatostatin analogue. pNETs typically localized in the head and body of the pancreas with an average size of 4.6 cm (2.5–7 cm) and the source of ectopic ACTH secretion may remain hidden for several years. In our case, the pancreatic lesion measured 11 cm which was larger than the average size. Despite the challenges posed by the tumour’s size and complications such as IVC thrombosis, the multidisciplinary approach involving endocrinologists, surgeons and radiologists allowed for effective management. Surgical intervention was complemented by medical therapies such as metyrapone, ketoconazole, lanreotide and eventually osilodrostat to control hypercortisolism. Osilodrostat demonstrated good efficacy in reducing cortisol levels in our patient. Conclusion This case highlights the aggressive nature of EAS-pNETs and the challenges in the management, particularly when presenting with advanced metastatic disease. The use of osilodrostat represents a promising advancement in the management of EAS.